Bringing Context Awareness to IoT-Based Wireless Sensor Networks - Gaur, Shashank (2015)
IEEE International Conference on Pervasive Computing and Communications (PerCom). 23 to 26, Mar, 2015, PhD Forum. Saint Louis, U.S.A..